Developing leadership skills for health and social care professionals - Phillips, Annie (Radcliffe Publishing, 2013)
This highly practical guide, and its companion volume Developing Assertiveness Skills for Health and Social Care Professionals are essential tools for all health and social care professionals, particularly those in acute medicine, primary care and the community. It is also highly recommended to those without a management role wanting to understand how to develop their relationships with their colleagues and managers